Product Development of Ready-to-Eat Fermented Fish Dipping Sauce in a Retort Pouch - Taraprom, Nutthapong; Suteebut, Nomjit; Pedcharat, Kasarin; Tungsatitporn, Duangkamol (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
The fermentation of fish includes whole fish, pieces, and strips, particularly Som-fug, which is commonly used in various traditional dishes. However, preparing fermented fish for consumption can be time-consuming. To align with modern consumer lifestyles, this study aims to develop a ready-to-eat fermented fish product called "Loun-Pla-Som-fug" in retort pouches. The study first explored basic simmering recipes, identifying the third recipe as the most preferred among sensory panelists. The product was then sterilized using a retort process at 116 oC for 25, 30, and 35 minutes. Results showed that longer sterilization times led to significantly darker color values, with increases in red (a*) and yellow (b*) components (p≤0.05). However, pH levels remained unaffected (p>0.05), and no microbial growth was detected across all time intervals during storage. Products sterilized at 116 oC for 25 minutes retained similar sensory characteristics as the pre-sterilized version and were deemed suitable for production. This ready-to-eat product adds value to traditional fermented fish and meets consumer demand for convenience.